2015
DOI: 10.7897/2230-8407.0615
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Α-Glucosidase Inhibitory Active Compounds From Ethanol Extract of Kayu Tuah (Antidesma Celebicum Miq.) Leaves

Abstract: Antidesma celebicum Miq. belongs to Euphorbiaceae family has been used as antidiabetic traditional medicine. The aim of the research was to isolate the α-Glucosidase inhibitory compound from ethanol extract of Antidesma celebicum leaves. The isolation have been done using column chromatography silica gel 60 and the structure was determinated base on spectral data of IR, MS, NMR. The result showed that the isolation obtained gallic acid as α-Glucosidase inhibitor with IC50 value of 0.057 mM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…It can be concluded that the total phenol content in EEAC was 18.712 ppm or 187.12 g GAE [ 27 ]. EEAC is known to have an antidiabetic effect by inhibiting α -glucosidase activity mainly due to its phenolic content (i.e., gallic acid) [ 10 ]. Phenols can control starch digestion by forming hydrogen bonds with polar digestive enzymes such as α -amylase and α -glucosidase.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It can be concluded that the total phenol content in EEAC was 18.712 ppm or 187.12 g GAE [ 27 ]. EEAC is known to have an antidiabetic effect by inhibiting α -glucosidase activity mainly due to its phenolic content (i.e., gallic acid) [ 10 ]. Phenols can control starch digestion by forming hydrogen bonds with polar digestive enzymes such as α -amylase and α -glucosidase.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, EEAC is known to have α -glucosidase inhibitory activity whose mechanism of action is similar to that of acarbose [ 10 ]. Oral administration of EEAC for 28 days drastically reduced blood glucose level compared to the diabetic control group, and this reduction in FBG level was similar to the acarbose-treated group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation